Merozoite Proteins Discovered by qRT-PCR-Based Transcriptome Screening of Plasmodium falciparum - Hou, Nan; Li, Shanshan; Jiang, Ning; Piao, Xianyu; Ma, Yu; Liu, Shuai; Chen, Qijun (Frontiers in Cellular and Infection Microbiology, 2021)
The development of malaria vaccines and medicines depends on the discovery of novel malaria protein targets, but the functions of more than 40% of P. falciparum genes remain unknown. Asexual parasites are the critical stage that leads to serious clinical symptoms and that can be modulated by malaria treatments and vaccines. To identify critical genes involved in the development of Plasmodium parasites within erythrocytes, the expression profile of more than 5,000 genes distributed across the 14 chromosomes of the PF3D7 strain during its six critical developmental stages (merozoite, early-ring, late-ring, early trophozoite, late-trophozoite, and middle-schizont) was evaluated. Hence, a qRT-PCR-based transcriptome of the erythrocytic developmental process of P. falciparum was revealed. Weighted gene coexpression network analyses revealed that a large number of genes are upregulated during the merozoite release process. Further gene ontology analysis revealed that a cluster of genes is associated with merozoite and may be apical complex components. Among these genes, 135 were comprised within chromosome 14, and 80% of them were previously unknown in functions. Western blot and immunofluorescence assays using newly developed corresponding antibodies showed that some of these newly discovered proteins are highly expressed in merozoites. Further invasion inhibition assays revealed that specific antibodies against several novel merozoite proteins can interfere with parasite invasion. Taken together, our study provides a developmental transcriptome of the asexual parasites of P. falciparum and identifies a group of previously unknown merozoite proteins that may play important roles in the process of merozoite invasion.